Design and Implementation of Software for Ship Monitoring System in Offshore Wind Farms. (2nd December 2019) - Tabi Fouda, Bernard Marie; Han, Dezhi; An, Bowen; Chen, Xiangzhi; Shen, Sixi
Abstract : To improve the safety of vessels in the offshore wind farms, this paper develops the design and implementation of a multiclient monitoring system that is a ship monitoring system software (SMSS). The design is based on automatic identification system (AIS) and geographic information system (GIS). The data of the target ships around the offshore wind farm zone will be displayed on a GIS map and monitored in the implemented software system in real time. The localization method and the warning zone judgment algorithm are used to carry out the vessel position around the offshore wind farm area. The software system includes some unavoidable features, namely, AIS encoding and decoding and automatic sending of short messages to ships arriving in the warning area. The tests of the SMSS show that in real time, the software system performs properly by detecting the target ships around the warning zone and sends short messages to these ships, which makes the SMSS more effective and reliable.